Foreword - Belafatti, Fabio (Acta Orientalia Vilnensia, 2017)
It is with great pleasure and pride that Vilnius University’s Centre of Oriental Studies presents the latest special issue of Acta Orientalia Vilnensia, featuring a collection of peer-reviewed articles on the religious and linguistic diversity of Turkic-speaking peoples in Eastern Europe. [...]